Insurer-Provider Networks in the Medical Care Market - Ho, Katherine (American Economic Review, 2009)
I use data on the hospital networks offered by managed care health insurers to estimate the expected division of profits between insurers and providers. I include a simple profit-maximization framework and an additional effect: hospitals that can secure demand without contracting with all insurers (e.g., those most attractive to consumers and those that are capacity constrained) may demand high prices that some insurers refuse to pay. Hospital mergers may also affect price bargaining. I estimate that all three types of hospitals capture higher markups than other providers. These results provide information on the hospital investment incentives generated by bargaining.